Handbook of burns: Reconstruction and rehabilitation Volume 2 - Kamolz, Lars-Peter (Springer Vienna Imprint: Springer, 2012)
This volume compiles the perspectives of a multi-author team examining the entire spectrum of burn reconstruction and long-term treatment. Individual chapters cover basic aspects of wound healing and scarring, and those of plastic surgery relating to tissue rearrangement and the use of flaps, as well as the long-term use of skin and skin substitutes. Furthermore, topics such as rehabilitation and scar management are addressed in detail. This part provides detailed reconstruction guidelines divided by anatomic region (e.g. face, hands,...), as well as aspects of future trends and prospects in burn reconstruction, among which are e.g. allotransplantation and bionics.